PENGARUH FREE CASH FLOW, RISIKO BISNIS PADA NILAI PERUSAHAAN DENGAN KEBIJAKAN HUTANG SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BEI PERIODE 2011-2015 - Puspita Sari, Ni Putu Santhi; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2017)
The purpose of this study to determine the effect of free cash flow and business risks on the value of the company and how the debt policy may mediate the effect of these two factors on the value of the company. This research was conducted on property and real estate company listed on the Indonesia Stock Exchange in 2011-2015. The number of samples taken as many as 29 companies with purposive sampling technique. Data analysis technique used is the analysis of the path (Path Analysis). The results showed that the high free cash flow led to the company increasing debt policy so that the optimization of the company value can be achieved and Debt policy is an intervening variable.. Business risks can increase when companies use high debt to meet the needs of funding, which will decrease value of the company and Debt policy is not an intervening variable.
Keywords: Free Cash Flow, Business Risk, Debt Policy, Firm Value